Radiation exposure and clinical outcome in patients undergoing percutaneous intradiscal ozone therapy for disc herniation: Fluoroscopic versus conventional CT guidance. - Francesco Somma; Vincenzo D'Agostino; Alberto Negro; Valeria Piscitelli; Stefania Tamburrini; Carmine Sicignano; Fabrizio Fasano; Silvio Peluso; Alessandro Villa; Gianvito Pace; Giuseppe Sarti; Giuseppe Maria Ernesto La Tessa; et al. (PLoS ONE, 2022)
Purpose To compare technical success, clinical success, complications and radiation dose for percutaneous intradiscal ozone therapy in patients with lumbar disc herniation using fluoroscopic guidance versus conventional computed tomography (CT) guidance. Materials and methods Between March 2018and March 2021, 124consecutive percutaneous intradiscal ozone therapies wereperformedon111 patients with low back pain (LBP) and/or sciatic pain due to lumbar disc herniation, using fluoroscopic or conventional CT guidance, respectively in 53 and 58 herniated lumbar discs, with at least 1-month follow up. Dose area product (DAP) and dose length product (DLP) were recorded respectively for fluoroscopy and CT, and converted to effective dose (ED). Results Fluoroscopic and CT groups were similar in terms of patient age (p-value 0.39), patient weight (p-value 0.49) and pre-procedure Oswestry Disability Index (ODI, p-value 0.94). Technical success was achieved in all cases. Clinical success was obtained in 83.02% (44/53) patients in fluoroscopic group and 79.31% (46/58) in CT group. Mean DAP was 11.63Gy*cm2 (range 5.42-21.61). Mean DLP was 632.49mGy-cm (range 151.51-1699). ED was significantly lower in the fluoroscopic group compared toCT group (0.34 vs. 5.53mSv, p = 0.0119). No major complication was registered. Minor complications were observed in 4 cases (2 in fluoroscopic group; 2 in CT group). Conclusions Compared to conventional CT guidance, fluoroscopic guidance for percutaneous intradiscal ozone therapy in patients with lumbar disc herniation shows similar technical and clinical success rates, with lower radiation dose. This technique helps sparing dose exposure to patients.